2018
DOI: 10.1016/j.yexcr.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-IIA heavy chain phosphorylation on S1943 regulates tumor metastasis

Abstract: Nonmuscle myosin-IIA (NMHC-IIA) heavy chain phosphorylation has gained recognition as an important feature of myosin-II regulation. In previous work, we showed that phosphorylation on S1943 promotes myosin-IIA filament disassembly in vitro and enhances EGF-stimulated lamellipod extension of breast tumor cells. However, the contribution of NMHC-IIA S1943 phosphorylation to the modulation of invasive cellular behavior and metastasis has not been examined. Stable expression of phosphomimetic (S1943E) or non-phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…S3A and S3B ). The prediction of Group-based Prediction System, Version 2.0 (GPS 2.0; http://gps.biocuckoo.org/ ) showed that the fragment of EATR contained two phosphorylation sites, S1916 and S1943, which were reported to regulate the assembly of myosin-IIA filaments 24 , 37 . To identify the HBXIP-promoted phosphorylation sites of EATR, the S1916 and S1943 sites were mutated to alanine (A, mimics of phosphorylation deficiency).…”
Section: Resultsmentioning
confidence: 99%
“…S3A and S3B ). The prediction of Group-based Prediction System, Version 2.0 (GPS 2.0; http://gps.biocuckoo.org/ ) showed that the fragment of EATR contained two phosphorylation sites, S1916 and S1943, which were reported to regulate the assembly of myosin-IIA filaments 24 , 37 . To identify the HBXIP-promoted phosphorylation sites of EATR, the S1916 and S1943 sites were mutated to alanine (A, mimics of phosphorylation deficiency).…”
Section: Resultsmentioning
confidence: 99%
“…WT and S100A4 KO MLFs were plated onto fibronectin-coated glass coverslip-bottom dishes and transfected with the EGFP NMII-A fusion protein expressing plasmid, pEGFP-C3-NMHC-IIA (kindly provided by Dr Anne Bresnick ( 88 )). After 6 h, transfection media was replaced with 10% SCM for 48 h. FRAP experiments were performed on an inverted Leica SP8 confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Ser-1943 phosphorylation is required for in vitro matrix degradation and increased invadopodia function, as well as increased in vivo metastasis. Therefore, NMIIA function regulates breast cancer cell invasion and metastasis ( 79 ). NMIIA-mediated cortical mechanics has also been implicated in colorectal cancer.…”
Section: Implications For Disease Severity and Clinical Outcomementioning
confidence: 99%